Carbon Dioxide Emissions from Operation of Czech Building Stock and Potential for Their Reduction. (June 2019) - Lupíšek, A
Abstract: The paper presents a study that modelled potential for savings of CO2 emissions from the Czech building stock in ten scenarios. Input data in scenarios were taken from analyses of energy saving potentials of Czech building stock from NGO Chance for Buildings. The results provided values of modelled CO2 emissions of the Czech building stock for each year in period 2016–2075. Cumulative data for periods 2015–2030, 2031–2050 and 2051–2075 were compared to the proposed national carbon budget coming from the UN Emissions Gap Report. The study estimated production of CO2 from Czech building stock in 2016 at 44.57 Mt, which represented share of 43% in the total national CO2 production. The scenario S5 in RCP 8.5 showed potential for annual reduction of CO2 emissions from current 44.57 to 15.29 Mt in 2075 (reduction by 66%). The needed reduction of CO2 emissions calculated from the global carbon budget for climatic goal 2° is much larger. It is very likely, that even the most stringent of the proposed energy saving scenarios would not be sufficient for the Czech building stock to comply with the Paris Agreement.